2003
DOI: 10.1029/2002gc000304
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic magnetic behavior of subaerial and submarine lava units from the Hawaiian Scientific Drilling Project (HSDP‐2)

Abstract: [1] This study presents rock magnetic properties and the magnetic mineralogy of subaerial and submarine lava flows of Mauna Loa and Mauna Kea volcanoes collected from the 3109 m deep HSDP-2 drill hole in Hawaii. Three different groups of magnetic behavior are recognized in the subaerial lava flows related to the degree of high temperature oxidation during extrusion. Group 1 shows homogenous titanomagnetite with low X mt , low Curie temperatures (T C : 100°-200°C) and weak median demagnetizing fields (< 20 mT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 35 publications
8
38
0
1
Order By: Relevance
“…Indeed, at least some of our susceptibility curves resemble curves measured on synthetic samples of this composition (Ishikawa et al, 1985). Similar χ -T curves have been also reported for some Hawaiian basalts (Kontny et al, 2003;Yamamoto, 2006) where presence of (hemo) ilmenite was demonstrated by microscopic observations. On the other hand, Kosterov (2001) did not observe peaks attributable to (hemo) ilmenite is basalts from Karoo, Parana, and North Atlantic Large Igneous Provinces (LIPs), despite the fact that abundant exsolved titanomagnetite grains, where hemoilmenite should be present in lamellae (cf.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Indeed, at least some of our susceptibility curves resemble curves measured on synthetic samples of this composition (Ishikawa et al, 1985). Similar χ -T curves have been also reported for some Hawaiian basalts (Kontny et al, 2003;Yamamoto, 2006) where presence of (hemo) ilmenite was demonstrated by microscopic observations. On the other hand, Kosterov (2001) did not observe peaks attributable to (hemo) ilmenite is basalts from Karoo, Parana, and North Atlantic Large Igneous Provinces (LIPs), despite the fact that abundant exsolved titanomagnetite grains, where hemoilmenite should be present in lamellae (cf.…”
Section: Discussionsupporting
confidence: 68%
“…Kontny et al (2003) have measured susceptibility and hysteresis loops as a function of temperature for Hawaiian basalts, also of hotspot origin. Additional low-temperature susceptibility data for Hawaiian volcanics have been reported by Yamamoto (2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such broad humps near the Verwey transition are typical for titanomagnetites, which suffered a high-temperature oxidation in conjunction with a decreasing Ti-content and the development of ilmenite exolution lamellae (e.g. Kontny et al 2003).…”
Section: 2 T E M P E R a T U R E -D E P E N D E N T M A G N E T Imentioning
confidence: 99%
“…Magnetic methods like temperature-dependence of magnetic susceptibility often indicate more than one magnetic phase within basaltic rocks and a large variation in ilmenohematite and titanomagnetite abundance and grain size strongly influences the interpretation of magnetic properties (e.g. Kontny et al, 2003b, Just et al, 2004. A rapid method to distinguish between those two phases is the ferrofluid method, which has been used for decades to detect magnetic material and their domain structures under an optical microscope (Bitter, 1931).…”
Section: Introductionmentioning
confidence: 99%